A SiGe-based fully-integrated 122-GHz FMCW radar sensor in an eWLB package. Issue 6 (10th February 2017) - Furqan, Muhammad; Ahmed, Faisal; Feger, Reinhard; Aufinger, Klaus; Hartner, Walter; Stelzer, Andreas
Abstract : High-performance SiGe HBTs and advancements in packaging processes have enabled system-in-package (SiP) designs for millimeter-wave applications. This paper presents a 122-GHz bistatic frequency modulated continuous wave (FMCW) radar SiP. The intended applications for the SiP are short-range distance and angular position measurements as well as communication links between cooperative radar stations. The chip is realized in a 130-nm SiGe BiCMOS technology and is based on a fully differential frequency-multiplier chain with in phase quadrature phase receiver and a binary phase shift keying modulator in the transmit chain. On-wafer measurement results show a maximum transmit output power of 2.7 dBm and a receiver gain of 11 dB. The chip consumes a DC power of 570 mW at a supply voltage of 3.3 V. The fabricated chip is integrated in an embedded wafer level ball grid array (eWLB) package. Transmit/receive rhombic antenna arrays with eight elements are designed in two eWLB packages with and without backside metal, with a measured peak gain of 11 dBi. The transceiver chip size is 1.8 mm × 2 mm, while the package size is 12 mm × 6 mm, respectively. FMCW measurements have been conducted with a sweep bandwidth of up to 17 GHz and a measured range resolution of 1.5 cm has been demonstrated. 2D positions of multiple targets have been computed using two coherently linked radar stations.